Membedah Diskursus Sinodalitas Paus Fransiskus dan Relevansinya terhadap Kehidupan Menggereja di Indonesia - Rikardus Jehaut (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
Abstract: This article intends to critically dissect Pope Francis’ discourse on synodality at the commemoration of the 50th anniversary of the institution of the Synod of Bishops on 17 October 2015. First of all, it tackles theconcept of synodality briefly and then elaborate on the various aspects of synodality. By using the method of content analysis and literature study, the author - in the light of Pope Francis’ discourse - seeks to provide somecritical notes on what the spirit and practice of synodality does means and does not mean. The novelty of this article lies in its attempt to see the relevance of the discourse for the Indonesian context. The author argues that the themes of clericalism, democratization in the Church, the development of civil society based on justice and brotherhood, dialogue between religions are relevant for our context. The author concludes that a correct understanding of synodality as a constitutive dimension of the Church must be possessed by all the faithful because it greatly determines the existence and the life of the Church as well as Her mission in the world. Key words: Diskursus, sinodalitas, Paus Fransiskus, Gereja, Konteks Indonesia